2011
DOI: 10.1530/eje-10-0758
|View full text |Cite
|
Sign up to set email alerts
|

A novel TMEM127 mutation in a patient with familial bilateral pheochromocytoma

Abstract: Objective: In this report, we describe a new patient with unexplained familial bilateral pheochromocytoma. Following the recent description of TMEM127 as a new pheochromocytoma susceptibility gene, the aim of this study was to test the hypothesis of a causative TMEM127 gene mutation in this patient. Design: Pheochromocytoma susceptibility genes were analyzed in germline DNA and losses of heterozygosity (LOH) assessed by BAC array comparative genomic hybridization in tumor DNA. SDHB expression and S6 kinase (S6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 14 publications
4
26
0
2
Order By: Relevance
“…The typical presentation is a unilateral adrenal pheo in patients with no prior family history. Recently, however, bilateral pheo, extraadrenal pgl, and hnpgl have been described 27,28 . The penetrance is unknown.…”
Section: Genetics Of Pheo-pgl: Non-syndromic Causesmentioning
confidence: 99%
“…The typical presentation is a unilateral adrenal pheo in patients with no prior family history. Recently, however, bilateral pheo, extraadrenal pgl, and hnpgl have been described 27,28 . The penetrance is unknown.…”
Section: Genetics Of Pheo-pgl: Non-syndromic Causesmentioning
confidence: 99%
“…An association between TMEM127 mutation and pheochromocytoma was initially discovered through global expression profiling and high-density copy number mapping, with TMEM127 mutations being identified in almost one-third of familial cases. 21,81 Subsequent direct sequencing analyses have now demonstrated that 2%-4% of individuals with SHN-PG possess TMEM127 mutations. 63,74 Although the exact mechanism by which TMEM127 mutations result in paraganglioma tumorigenesis is the focus of current research, preliminary studies indicate it is a negative regulator of mTOR (mammalian target of rapamycin), a cellular growth and proliferation protein of the PI3-kinase family.…”
Section: Tmem127 and Maxmentioning
confidence: 99%
“…Ce gène a été identifié en 2010 comme un gène de susceptibilité au PCC grâce à des approches de génomique intégrative, combinant analyse de liaison, étude du transcriptome et analyse du nombre de copies [13]. Les échantillons tumoraux provenant de patients avec une mutation TMEM127 se classent dans le cluster 2 ; il y a systématiquement une perte de l'allèle sauvage qui s'étend souvent sur la totalité du bras 2q [13,29,30]. Les premières données obtenues in vitro suggèrent que TMEM127 pourrait être impliquée dans le trafic protéique intracellulaire et/ou dans le recyclage des protéines de l'endocytose.…”
Section: Les Nouveaux Gènes De Prédisposition Aux Pgl/pccunclassified